(untitled) (Research, Society and Development, 2021)
The vestibular bifurcation cyst is an uncommon inflammatory odontogenic cyst that develops on the vestibular face of the permanent lower first molar in children aged 5 to 13 years. Clinically, it presents sensitivity, edema, periodontal pocket and secretion with an unpleasant taste. Radiographically, it is shown as a unilocular and well-defined radiolucent lesion involving the vestibular bifurcation and the root region of the tooth in question. The root apices of the molars are characteristically facing the mandibular lingual cortex. This study aimed to report a clinical case of a child with a vestibular bifurcation cyst. It is a male patient, 7 years old, presenting edema in the region of the right jaw, pain on palpation, presence of periodontal abscess with purulent secretion in the region of tooth 85 and 46. In the CFFC he showed a well-defined radiolucent image, expansive and unilocular involving the crown and vestibular bifurcation of element 46, disrupting the vestibular alveolar bone cortex, compatible with Vestibular Bifurcation Cyst. It was concluded that the vestibular bifurcation cyst is a pediatric disease that occurs in the bifurcation area of ​​the buccal surface of an erupting permanent lower first molar and appears mainly in the first decade of life.